Pengaruh Transparansi, Partisipasi Masyarakat, dan Kejelasan Sasaran Anggaran pada Efektivitas Pengelolaan Dana Desa - Ego, I Komang; Suartana, I Wayan (Jurnal Samudra Ekonomi dan Bisnis, 2025)
This study aims to determine the effect of transparency, community participation, and clarity of budget targets, on the effectiveness of village fund management in Kubu District. This study was conducted in nine villages in Kubu District with a total of 54 respondents selected through a saturated sampling method. The selected respondents were village officials involved in the village fund management process. Data were collected using questionnaires that were distributed directly, and then analyzed using multiple linear regression methods with the help of the SPSS 25 program. The results showed that all variables analyzed, namely transparency, community participation and clarity of budget targets, were proven to have a positive effect on the effectiveness of village fund management.